1999
DOI: 10.1161/01.cir.100.suppl_2.ii-262
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cell Junctions Between Grafted and Host Cardiomyocytes at the Border Zone of Rat Myocardial Infarction

Abstract: Background-Cardiomyocyte transplantation is an innovative strategy for the treatment of heart failure after myocardial infarction. Cell junctions show diverse temporal polarization toward intercalated disks during postnatal development and exhibit altered distribution in diseased hearts. To elucidate the formation of cell junctions between grafted and host cardiomyocytes at the border zone of myocardial infarction, the 3D distribution of cell junctions was examined using immunohistochemistry and confocal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…14 Subsequent studies from multiple investigators showed that fetal or neonatal cardiomyocytes could form new myocardium in injured hearts as well. [15][16][17][18] The initial enthusiasm generated by these studies cooled somewhat, however, when it was shown that massive cell death, coupled with only limited cell proliferation after transplantation, prevented formation of enough new myocardium to replace more than a tiny fraction of an infarct. 19,20 Still, functional improvement was reported even with small grafts, 18,[21][22][23] prompting the search for a cardiac cell source for human applications.…”
Section: The Early Years: Transplantation Of Committed Cells In Preclmentioning
confidence: 99%
“…14 Subsequent studies from multiple investigators showed that fetal or neonatal cardiomyocytes could form new myocardium in injured hearts as well. [15][16][17][18] The initial enthusiasm generated by these studies cooled somewhat, however, when it was shown that massive cell death, coupled with only limited cell proliferation after transplantation, prevented formation of enough new myocardium to replace more than a tiny fraction of an infarct. 19,20 Still, functional improvement was reported even with small grafts, 18,[21][22][23] prompting the search for a cardiac cell source for human applications.…”
Section: The Early Years: Transplantation Of Committed Cells In Preclmentioning
confidence: 99%
“…In the case of grafted fetal cardiomyocytes, cells tend to align parallel to the host cardiomyocytes; connexin-43, desmoplakin, and cadherin, which are major adhesion and gap junction proteins of the intercalated disk required for cell-to-cell electrical coupling, are localized between grafted cells and between grafted and host cardiomyocytes. 13,14 Thus, fetal cardiomyocyte grafts might contract in synchrony with the host tissue. In the case of skeletal myoblast grafts, cells can establish new muscle tissue (myotubes) when they are grafted into injured hearts.…”
Section: Histological Studiesmentioning
confidence: 99%
“…We considered that the survival of xenografted neonatal cardiomyocytes in injured myocardium could not present difficulties because the majority of investigations have suggested the survival of allografted cardiomyocytes in injured myocardium. 2,[11][12][13]25 Furthermore, the severe microenvironment in the injured myocardium might be improved by combination therapy, such as inducing angiogenesis to improve blood flow of the injured myocardium. 26,27 In conclusion, long-term survival of xenografts of neonatal cardiomyocytes was achieved by creating a blockade of the CD28 pathway via adenovirus-mediated CTLA4-Ig expression and the transient blockade of the CD40 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Allografted fetal or neonatal cardiomyocytes have shown long-term survival, differentiation and maturation, gap junction formation with host cardiomyocytes, and improved heart function. 2,7,[11][12][13] Despite their success, allografts of fetal cardiomyocytes may not be clinically feasible, first, because of their limited supply, and second, for ethical reasons. However, xenografts of fetal cardiomyocytes might be considered as an alternative if the problem of immunologic rejection could be overcome.…”
mentioning
confidence: 99%